Protestant Theology and the Making of the Modern German University. By Thomas Albert Howard - Chapman, Mark D. (The journal of theological studies, 2008)
This book offers a wide-ranging survey of the relationship between protestant theology and the development of the modern university in nineteenth- and early twentieth-century Germany. Primarily a work of institutional history which focuses on ‘the fortunes of the theological faculty as a component of the university, not on theology per se’ (p. 10), it presents a synthesis of a vast body of reading and research in what will be the standard English-language work on the subject for some time. Howard's scope is enormous—a quarter of the book (ch.